ANALISIS FAILURE MODE EFFECT (FMEA) PADA PENGADAAN OBAT DAN PERBEKALAN KESEHATAN PADA ERA JAMINAN KESEHATAN NASIONAL DI PUSKESMAS WONOKROMO SURABAYA - Nuning Farida; Amelia Lorensia; Budhi Setianto; Agus Aan Adriansyah (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Drug services in Public Healthcare are an important component whose availability influences the success of health efforts. District / City Health Office is a regional government work unit in the health sector, one of the tasks and authorities of which is to provide and manage public medicines for the district/city area. Effective pharmaceutical management in health service facilities is very important for patient welfare so risks must be identified and controlled. One of the efforts made by the City Health Office is to procure drugs using other methods that are legal according to government procurement of goods/services besides e-purchasing, which is called non-e-purchasing of drugs. Risks in the pharmaceutical supply chain are related to product discontinuity, product shortages, poor performance, patient safety, expense errors, and technological errors, all of which can result in system disruption. This study aims to determine the suitability of the plan with the realization of e- purchasing of drugs, identify problems that hamper the implementation of e-purchasing of drugs, determine the impact of obstacles on procurement, cost efficiency of drug procurement and determine the potential savings of drug procurement by e-purchasing for the period 2015 to 2019 by using the FMEA method, the e-purchasing data was collected at the Wonokromo Public Health Center in Surabaya. Study Failure Mode Effect (FMEA) in the procurement of drugs and UHC health supplies in Surabaya Wonokromo Health Center for the period of 2015-2019, it can be concluded that the absorption of capitation funds is more considered using the availability variable compared to the uptake of funds based on the rupiah value because the availability of more guarantees the need for treatment in the sustainable health centre. In this case, the perception of procurement actors in the analysis of UHC procurement process obstacles there are 41 obstacles, the role of E-purchasing is a very helpful system even though the implementation has not been perfect.